BS29 Expression of stable SOCS3 in human saphenous vein smooth muscle cells: potential therapy for vascular restenosis. (May 2019) - Moshapa, Florah; Williams, Jamie; Ellies, Jacobo; Riches-Suman, Kirsten; Palmer, Timothy
Abstract : Introduction: Suppressor of cytokine signalling 3 (SOCS3) limits JAK/STAT pathways involved in vascular inflammation and remodelling responsible for vein graft failure. However, SOCS3 is limited by its short biological half-life. Therefore, mutation of all 9 Lys residues that are potential sites of ubiquitination to Arg should produce a mutated SOCS3 resistant to ubiquitin-mediated proteasomal degradation ("Lys-less" SOCS3). We hypothesise that a stablised "Lys-less" SOCS3 may have greater therapeutic potential versus wild type (WT) SOCS3 in limiting JAK/STAT mediated processes responsible for neointimal hyperplasia and vein graft failure in type 2 diabetes mellitus (T2DM). Methods: Smooth muscle cells (SMCs) and endothelial cell (ECs) isolated from human saphenous vein (HSV) were transduced with recombinant lentiviruses, MOI= 3.6 (WT), 22.2 (Lys-less SOCS3) and 5.6 (GFP) tu/cell. Successful transduction was confirmed by immunofluorescence and immunoblotting. Ubiquitylation was tested by immunoprecipitation and immunoblotting and half-life was determined by immunoblotting following incubation ± protein synthesis inhibitor emetine. HSVSMC proliferation (cell counting and CyQuant proliferation assay) and migration (Boyden chamber assay) were assessed in transduced HSVSMCs. Finally, the effect of WT and Lys-less SOCS3 gene delivery on IL-6 and PDGF-BB signalling in HSVSMCs was assessed by phosphorylation of STAT3 (Tyr705) and ERK1/2 (Thr202/Tyr204) by immunoblotting. Results: Lentiviral transduction of WT and Lys-less SOCS3 in HSVSMCs and ECs was highly efficient after 48hrs with 97±0.9% (n=4) and was sustained for at-least 2 weeks. Lys-less SOCS3 was resistant to ubiquitylation in HSVECs in contrast to WT (n=3). Lys-less SOCS3 was also more stable (t1/2=4 h) than WT (t1/2<4 h) (n=6, p<0.001). Concomitant with a significant reduction in proliferative response to sIL-6Rα/IL-6 in HSVSMCs treated with WT and Lys-less SOCS3 was a selective inhibition of sIL-6Rα/IL-6-mediated STAT3 activation by 74±6% and 80±6% respectively (n=5, p<0.001 versus sIL-6Rα/IL-6 alone) but not ERK1/2. Time course experiments indicated that PDGF-BB-induced STAT3 and not ERK1/2 activation was blocked by WT SOCS3 in HSVSMCs by 59±4% at 5 minutes and 38±1% at 15 minutes (n=3 p<0.05 versus PDGF-BB/GFP). WT and Lys-less SOCS3 did not affect proliferative responses to 20% foetal bovine serum as well as PDGF-BB-induced migration. Conclusion: WT and Lys-less SOCS3 can be successfully transduced into HSVSMCs and ECs with high efficiency using recombinant lentiviruses. Lys-less SOCS3 is more stable than WT yet functionally equivalent in inhibiting HSVSMC proliferation. WT SOCS3 was also capable of inhibiting both IL-6 and PDGF-BB signalling. These results provide evidence for the possible therapeutic targeting of SOCS3 to limit SMC dysfunction responsible for graft failure. Conflict of interest: None